Glycosylation of the polyphenols from Resina draconis by glycosyltransferase YjiC1 - Wang, Chen; Tang, Ding; Xu, Wei; Liu, Yan; Huang, Zhao-He; Shaw, Pang-Chui; Jiang, Ren-Wang (Natural product research, 2023)
Resina Draconis (RD), also known as 'dragon's blood', contains a broad range of natural compounds, such as flavonoids, stilbenes and dihydrochalcones. It is clinically used to enhance blood circulation. However, the major components of RD suffer from relatively poor water solubility. Glycosylation is a critical determinant for modulating solubility and improving bioavailability and bioactivity of natural products. Herein, we report a novel method to efficiently synthesize glycosidic derivatives of the major polyphenols in RD using a microbial glycosyltransferase, i.e., YjiC1. Solubility test showed that the synthetic glycosidic derivatives displayed higher water solubility than the raw materials. This research sheds light on the structural modification of natural products for higher water solubility, which is important for innovative drug discovery.